Phenotyping and drought tolerance in upland rice - Moura, Amanda Mendes de (2021)
Drought stress has been considered one of the greatest risks to food security and sustainability for the rice crop worldwide. However, tolerance to this stress is considered complex and trails involving this trait are difficult to conduct. Furthermore, to recommend genotypes with greater tolerance, it is necessary evaluations be carried out in a large number of environments, associating different water conditions, locations and agricultural years. Is common in studies involving multi-environment with this propose only use one trait for evaluation, which can lead to a less efficient genotype recommendation. Thus, this work, divided into two parts, aimed to phenotyping and study of the agronomic behavior of rice genotypes, cultivated in upland environments with stress and non-stress conditions, further, the identification of genotypes with drought tolerance, using different index. Moreover, conduct a study of stability associated with high productive performance for multi-traits and multi-environments using the WAASB method. It was evaluated three cultivars chekcs, Douradão, BRS Esmeralda and BRS Soberana, and 22 contrasting lines of a cross between BRS Soberana and Douradão, cultivars with different responses to tolerance to water deficit. The trails were carried out in two locations, in Lavras-MG and Porangatu-GO, Southeast and Midwest of Brazil, in two consecutive agricultural years. for each year, the experiments were carried out under two water conditions, well water conditions (WWC) and drought stress condition during reproductive phase (WSC). In the first study, nine characteristics were evaluated: grain yield (GY), number of days to flowering (DF), plant height (PH), 1000-grains weight (GW), number of spikelets per panicle (SP), spikelet sterility ratio (SS), flag leaf length (FLL), flag leaf width (FLW) and flag leaf length to width ratio (FLR). The stress applied during the reproductive growth stage was classified as severe, resulting in a 67% grain yield reduction in water stress conditions. GY and SS were the characters most affected by water deficit and should have the greater consideration on selection for drought tolerance. In addition, it was possible to associate genotypes that combined high grain yield and drought tolerance. Douradão, BRS Esmeralda and lines 19, 15, 6, 3 and 5 were considered the most tolerant and presented the highest parental candidates for the breeding program for drought tolerance. In the second study, the following characters were evaluated: GY, DF, SP, SS and GW. The WAASB methodology proved to be useful for selection targeting multi-traits and indicated that Douradão and lines 2, 21 and 11 were the ones with greater stability associated with higher performance for set of environments studied.